2001
DOI: 10.1074/jbc.m010902200
|View full text |Cite
|
Sign up to set email alerts
|

Dimerization and Nuclear Localization of Ku Proteins

Abstract: Ku, a heterodimer of Ku70 and Ku80, plays a key role in multiple nuclear processes, e.g. DNA repair, chromosome maintenance, and transcription regulation. Heterodimerization is essential for Ku-dependent DNA repair in vivo, although its role is poorly understood. Some lines of evidence suggest that heterodimerization is required for the stabilization of Ku70 and Ku80. Here we show that the heterodimerization of these Ku subunits is important for their nuclear entry. When transfected into Ku-deficient xrs-6 cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

12
64
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 68 publications
(76 citation statements)
references
References 32 publications
12
64
0
Order By: Relevance
“…The nuclear translocation of Ku70 is, at least in part, controlled at a nuclear localization signal (NLS)-recognition step by NLS receptors and regulated by the heterodimerization with Ku80 [12][13][14][15]17]. In hamster cells, Ku70/Ku80 heterodimer accumulation at DSBs produced using a 405-nm laser starts immediately after irradiation [18], strongly supporting the idea that the heterodimer of Ku70 and Ku80 is a sensor of DSBs in the nuclei.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…The nuclear translocation of Ku70 is, at least in part, controlled at a nuclear localization signal (NLS)-recognition step by NLS receptors and regulated by the heterodimerization with Ku80 [12][13][14][15]17]. In hamster cells, Ku70/Ku80 heterodimer accumulation at DSBs produced using a 405-nm laser starts immediately after irradiation [18], strongly supporting the idea that the heterodimer of Ku70 and Ku80 is a sensor of DSBs in the nuclei.…”
Section: Discussionmentioning
confidence: 82%
“…It was also reported that Ku70 is translocated from the cytoplasm to the nucleus in rat and mouse fibroblasts after X-irradiation [2,29]. On the other hand, we have demonstrated that the nuclear translocation of Ku70 is, at least in part, controlled at a nuclear localization signal (NLS)-recognition step by NLS receptors and regulated by heterodimerization with Ku80 [12][13][14][15]17].…”
mentioning
confidence: 64%
“…However, a separate study has shown that equivalent amounts of Ku86 are immunoprecipitated with antiserum specific to either Ku70 or the Ku heterodimer, and dimerization is necessary for efficient nuclear translocation of each subunit (42). These results therefore indicate that nuclear Ku70 occurs as a heterodimer and that Ku associated with matrix does so as a heterodimer of Ku70 and Ku86.…”
Section: Discussionmentioning
confidence: 87%
“…This protein complex, which is located primarily in the nucleus (Bertinato et al, 2001;Koike et al, 2001), has key roles in numerous cellular processes, including DNA repair, chromosome maintenance and regulation of transcription (Ramsden and Gellert, 1998). In most instances, the Ku heterodimer is in a complex with the catalytic subunit of DNA-dependent protein kinase (DNA-PKcs).…”
mentioning
confidence: 99%